Redesain Kemasan Suvenir Ondel-Ondel Betawi - Wijayanti, Sri Hapsari; Harrison, Alfonso; Gunawan, Reinandus Aditya; Tobing, Michelle Angela Allegra; Natalie, Jessica (Abdimas Mandalika, 2025)
Abstract: Sanggar Seni Citra Argawana is one of the Ondel-Ondel Souvenir craftsmen in the Setu Babakan-Jagakarsa area, South Jakarta since 1995, which is the target of this community service activity. The problem faced by the target of the service is their difficulty in designing attractive packaging for the Ondel-Ondel Souvenir products that they offer to their consumers. The packaging problem is a problem that is often experienced by small and medium entrepreneurs in almost all cities in Indonesia. The appearance of the packaging needs to have an appeal to be touched, and then purchased. Unattractive packaging will result in consumers not being moved to touch, let alone buy. Therefore, this community service aims to help Sanggar Seni Citra Argawana UMKM in redesigning the packaging of Ondel-Ondel Souvenir products that have been used so far to become packaging that has more visual appeal but remains functional, which can help increase consumer purchasing interest. The method used in this service is a practical workshop in creating new packaging designs for craftsmen at Sanggar Seni Citra Argawana UMKM. The results obtained were that the craftsmen at the UMKM Sanggar Seni Citra Argawana succeeded in creating a new packaging design for their Ondel-Ondel souvenir products which had more visual appeal and were functional for their consumers.Abstrak: Sanggar Seni Citra Argawana adalah salah satu UMKM perajin Suvenir Ondel-Ondel di wilayah Setu Babakan-Jagakarsa, Jakarta Selatan sejak tahun 1995, yang menjadi target aktivitas pengabdian masyarakat ini. Permasalahan yang dihadapi oleh target pengabdian adalah kesulitan mereka mendesain kemasan yang menarik untuk produk Suvenir Ondel-Ondel yang mereka tawarkan kepada para konsumennya. Masalah kemasan merupakan masalah yang banyak dialami oleh pengusaha kecil dan menengah di hampir semua kota di Indonesia. Tampilan kemasan perlu memiliki daya tarik untuk disentuh, lalu kemudian dibeli. Kemasan yang kurang menarik akan berakibat konsumen tidak tergerak untuk menyentuh apalagi membeli. Oleh karena itu, pengabdian masyarakat ini bertujuan untuk membantu UMKM Sanggar Seni Citra Argawana dalam mendesain ulang (Redesain) kemasan produk Suvenir Ondel-Ondel yang selama ini telah digunakan agar menjadi kemasan yang lebih memiliki daya tarik visual namun tetap fungsional, yang dapat membantu meningkatkan minat beli dari konsumen. Metode yang digunakan dalam pengabdian ini adalah workshop praktis dalam membuat desain kemasan yang baru bagi para perajin di UMKM Sanggar Seni Citra Argawana. Hasil yang diperoleh adalah para perajin di UMKM Sanggar Seni Citra Argawana berhasil membuat desain kemasan baru untuk produk Suvenir Ondel-Ondelnya yang lebih memiliki daya tarik visual serta fungsional bagi para konsumennya.